Indirect Questioning in Sample Surveys - Chaudhuri, Arijit (Springer Berlin Heidelberg, 2013)
Indirect questioning is a crucial topic in surveys of human populations. When the issue is about a stigmatizing characteristic (for example about illegal drug use), standard survey methodologies are destined to fail because, as expected, people are not willing to reveal incriminating information or information violating their privacy.  Indirect questioning techniques have been devised so that the privacy of participants in a sample survey is protected and at the same time good estimates of certain parameters (e.g. the percentage of people in a certain community who use illegal drugs) can be delivered. The topic is modern and still under development. Indirect Questioning in Sample Surveys represents a collection of the most important and recent techniques of indirect questioning, including various versions of randomized response, the item count technique, the nominative technique, the three-card method, non-randomized response models and negative surveys, while also exploring the key aspect of protecting privacy.